HUBUNGAN FAKTOR IBU DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS PIYUNGAN KABUPATEN BANTUL - FAJRINA, Nurul (Universitas 'Aisyiyah Yk, 2016)
One of nutritional problems that under-five children often have is stunting, a condition when the body is short or very short happening due o nutritional deficiency and long term repeated diseases in fetus period until 2 first year of children’s life. The study was conducted to investigate the correlation between mother’s with stunting occurrence among under-five children. The study is an analytical survey with case control approach which was analyzed retrospectively. Statistical test used Chi Square test. Dependent variable of the study was stunting, and independent variable was mother’s factors consisting of education, mother’s age when they were pregnant, birth distance, body weight, and nutritional status when they were pregnant. The samples of the study were 41 respondents and 41 control samples, so the numbers of the samples were 82. The study was conducted from December 2015 - August 2016. The result of the study showed that the analysis result with chi square test indicated the correlation (p<0.05) and education with p-value = 0.04; (Odds Ratio (OR) = 3.777; 95% CI:1.505 – 9.475), the age when pregnant p-value = 0.034, (OR: 4.08; 95% CI:1,003-16.155), mother height (p-value = 0.022; (OR = 2.952;95% CI:1.154-7.556)), and nutritional status during pregnancy (p-value=0.01, OR=4.154; 95%CI:1.341-12.870). Meanwhile, birth distance did not have significant correlation with p-value = 0.062 (p>0.05; OR=2.708; 95%CI: 0.913-8.035).There was significant correlation among education, age when pregnant, mother’s height, and nutritional status during pregnancy with stunting cases on under-five children. It is expected that health professionals to have more intensive in health promotion and to give counseling related to pregnant preparation as one of the efforts to prevent stunting on under-five children. It is also expected to policy makers to use the same equipments as height measurement in baby health service by using standardized equipment.